Exploring the similarities between risk factors triggering depression in humans and elevated in-cage “inactive but awake” behavior in laboratory mice - Schmitt, Oceane; Finnegan, Emily; Trevarthen, Anna; Wongsaengchan, Chanakarn; Paul, Elizabeth S.; Mendl, Michael; Fureix, Carole (Frontiers in Veterinary Science, 2024)
Depression is a human mental disorder that can also be inferred in non-human animals. This study explored whether time spent inactive but awake (‘IBA’) in the home-cage in mice was further triggered by risk factors similar to those increasing vulnerability to depression in humans (early life stress, genetic predispositions, adulthood stress). Eighteen DBA/2J and 18 C57BL/6J females were tested, of which half underwent as pups a daily maternal separation on post-natal days 2-14 (early-life stress ‘ELS’) (other half left undisturbed). To assess the effect of the procedure, the time the dams from which the 18 subjects were born spent active in the nest (proxy for maternal behavior) was recorded on post-natal days 2, 6, 10 and 14 for 1h before separation and following reunion (matched times for controls), using live instantaneous scan sampling (total: 96 scans/dam). For each ELS condition, about half of the pups were housed post-weaning (i.e. from 27 days old on average) in either barren (triggering IBA and depression-like symptoms) or larger, highly enriched cages (n = 4-5 per group). Time mice spent IBA post-weaning was observed blind to ELS treatment using live instantaneous scan sampling in two daily 90-min blocks, two days/week, for 6 weeks (total: 192 scans/mouse). Data were analyzed in R using generalized linear mixed models. The dams were significantly more active in the nest over time (P=0.016), however with no significant difference between strains (P=0.18), ELS conditions (P=0.20) and before/after separation (P=0.83). As predicted, post-weaning barren cages triggered significantly more time spent IBA in mice than enriched cages (P<0.0001). However, neither ELS (P=0.4) nor strain (P=0.84) significantly influenced time mice spent IBA, with no significant interaction with environmental condition (ELS × environment: P=0.2861; strain × environment: P=0.5713). Our results therefore only partly support the hypothesis that greater time spent IBA in mice is triggered by risk factors for human depression. We discuss possible explanations for this and further research directions.